Identification of conserved erythrocyte binding regions in members of the Plasmodium falciparum Cys6 lipid raft-associated protein family (2009)
Detergent-resistant lipid raft membrane-associated Pf12, Pf38 and Pf41 proteins belong to the Cys6 family, whose members are implicated in Plasmodium falciparum invasion to erythrocytes. We have analyzed the interaction between 20-mer-long synthetic peptides spanning the entire Pf12, Pf38 and Pf41 sequences and erythrocytes. Eight high-activity binding peptides (HABPs) were identified in these proteins, which presented saturable bindings susceptible to erythrocytes' enzymatic treatment, and ?-turn, random coil and ?-helical elements as principal structural features. Some of these HABPs inhibited merozoite invasion in vitro, suggesting a possible role of Pf12, Pf38 and Pf41 during erythrocyte invasion and supporting their inclusion in the design of a fully effective antimalarial vaccine. © 2009 Elsevier Ltd. All rights reserved.